Balloon-borne cryogenic frost-point hygrometer observations of water vapour in the tropical upper troposphere and lower stratosphere over India: First results. (March 2016) - Sunilkumar, S.V.; Muhsin, M.; Emmanuel, Maria; Ramkumar, Geetha; Rajeev, K.; Sijikumar, S.
Abstract: Balloon-borne cryogenic frost-point hygrometer (CFH) observations of water vapour in the upper troposphere and lower stratosphere (UTLS) region carried out over India, from Trivandrum [8.5°N, 76.9°E] and Hyderabad [17.5°N, 78.6°E], were compared with that obtained from quasi-collocated Aura-Microwave Limb Sounder (MLS) satellite observations. Comparisons show a small dry bias for MLS in the stratosphere. Saturated or super-saturation layers observed near the base of tropical tropopause layer (TTL) are consistent with the quasi-collocated space-based observations of tropical cirrus from KALPANA-1 and CALIPSO. Disturbance of large scale waves in the upper troposphere appears to modulate the water vapour and cirrus distribution. Highlights: Cryogenic Frost-point hygrometer (CFH) observation of H2 O over India. CFH observations were compared with Aura-MLS. Saturation layers in TTL-base are consistent with tropical cirrus. Wave disturbance modulates water vapour and cirrus distribution in the UT.